Socio-environmental risks for untreated depression among formerly incarcerated Latino men - Miguel, Muñoz-Laboy (2014)
OBJECTIVE: To identify the levels of untreated depression and the socio-environmental factors associated with it among formerly incarcerated Latino men (FILM). METHODS: Cross-sectional survey with 259 FILM ages 18 to 49 who were released from prison/jail within the prior five years. Depression was measured by the Brief Symptom Inventory (BSI). Backward elimination was used to determine the best regression models. RESULTS: 26.9% of the study sample reported depression. Low familism, residing farther away from family members, low utilization of health and social services, high levels of loneliness and high lifetime and current frequency of alcohol use were also associated with depression. DISCUSSION: Depression is a major problem among FILM. Addressing untreated depression among FILM must be a public health priority.